INCLUSIVE EDUCATION: PRACTICAL EXPERIENCES AND MODERN APPROACHES (International journal of artificial intelligence, 2026)
This article examines the current state, theoretical foundations, and practical implementation of inclusive education in the global context. Inclusive education is defined not merely as the physical presence of students with disabilities in mainstream classrooms, but as a comprehensive systemic reform that embraces diversity and ensures equitable learning opportunities for all learners. The study analyzes modern pedagogical approaches, including Universal Design for Learning (UDL), differentiated instruction, and collaborative teaching models. Furthermore, it explores practical experiences from various countries, highlighting successful strategies and persistent challenges such as teacher preparedness, resource allocation, and attitudinal barriers. The article argues that the successful realization of inclusive education requires a shift from a medical model of disability to a social model, emphasizing the removal of environmental and societal barriers. Through a review of recent literature and case studies, this paper provides recommendations for policymakers, educators, and stakeholders to enhance the quality and effectiveness of inclusive practices.